2019
DOI: 10.3390/molecules24183301
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Haemophilus Activity of Selected Essential Oils Detected by TLC-Direct Bioautography and Biofilm Inhibition

Abstract: Essential oils (EOs) are becoming increasingly popular in medical applications because of their antimicrobial effect. Direct bioautography (DB) combined with thin layer chromatography (TLC) is a screening method for the detection of antimicrobial compounds in plant extracts, for example, in EOs. Due to their lipophilic character, the common microbiological assays (etc. disk diffusion) could not provide reliable results. The aim of this study was the evaluation of antibacterial and anti-biofilm properties of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 52 publications
1
19
0
Order By: Relevance
“…[ 52 ], our research group had to optimize the process for use with honey samples. Optimizing TLC–DB for two Haemophilus species involved altering conditions such as incubation time, and the composition of agar for growing the bacterium, the necessity of which was also confirmed in our previous study [ 65 ].…”
Section: Discussionmentioning
confidence: 60%
“…[ 52 ], our research group had to optimize the process for use with honey samples. Optimizing TLC–DB for two Haemophilus species involved altering conditions such as incubation time, and the composition of agar for growing the bacterium, the necessity of which was also confirmed in our previous study [ 65 ].…”
Section: Discussionmentioning
confidence: 60%
“…We have performed the synthesis of 20 nm hydrophilic silica nanoparticles with the previously reported modified Stöber method [9]. Briefly, a solution of tetraethoxysilane (TEOS) and ultrapure water in ethanol was prepared by using tetraethoxysilane, (Thermo Fisher GmbH, Kandel, Germany, pur.…”
Section: Methodsmentioning
confidence: 99%
“…One major characteristic and application of EOs are their strong antimicrobial activity, including antibacterial and antifungal effects without the development of microbial resistance. Numerous studies are found in the literature describing the antimicrobial activities of a large variety of EOs [8,9,10,11,12,13]. Most of these assays include conventional broth dilution method, disk diffusion method, and bioautography assay to measure the antimicrobial activity of EOs.…”
Section: Introductionmentioning
confidence: 99%
“…According to the GC-MS, geraniol (54.9%), thujanol (33.9%) and linalool (69.2%) were detected as main compounds in the three thyme oil chemotypes. Treatments with essential oils might be harmful to the cells [ 35 37 ], therefore their effects on cell viability in different dilutions (200-fold, 500-fold and 1000-fold) at 6 h and 24 h long treatments were examined DMSO was used as a carrier in the stock solutions, therefore, the effect of DMSO on the cells was also determined. DMSO did not affect significantly the cell viability (Fig.…”
Section: Resultsmentioning
confidence: 99%